1998
DOI: 10.1093/ortho/25.2.117
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extraction of third molars on late lower incisor crowding: a randomized controlled trial.

Abstract: The problem of late mandibular incisor crowding is a well established phenomenon, the cause of which has been the substance of considerable debate over the years. A central issue is the possible role of the third molars though no definitive conclusions have been consistently drawn. This prospective study was designed to investigate the effects of randomly assigned early extraction of third molars on late crowding of the mandibular incisors. One-hundred-and-sixty-four patients entered the study from 1984 follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
22

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 21 publications
2
87
0
22
Order By: Relevance
“…During the last century, many factors, such as treatment modalities, [8][9][10] preservation of original mandibular intercanine width, 11,12 continued growth, 13,14 influence of gingival tissues, 15,16 and role of third molars, 17,18 were investigated as contributors to relapse. A few studies have attempted to compare different retainers and protocols, ranging from minimal retention 19 to permanent retention.…”
Section: Introductionmentioning
confidence: 99%
“…During the last century, many factors, such as treatment modalities, [8][9][10] preservation of original mandibular intercanine width, 11,12 continued growth, 13,14 influence of gingival tissues, 15,16 and role of third molars, 17,18 were investigated as contributors to relapse. A few studies have attempted to compare different retainers and protocols, ranging from minimal retention 19 to permanent retention.…”
Section: Introductionmentioning
confidence: 99%
“…Their conclusions stated that evidence on the role of third molars as etiologic factor in the late lower arch crowding is lacking, similarly to the ones of the previous study [4]. The Scientific World Journal Harradine et al [5] described analogous outcome in subjects who underwent orthodontic treatment. They examined the effect of third molar extraction on the development of anterior mandibular dental crowding in a randomized controlled study.…”
Section: Introductionmentioning
confidence: 64%
“…This is an attractive concept as it implies that mandibular anterior crowding cannot be prevented and is just part of aging. Multiple studies have found no clinically significant reduction in mandibular anterior crowding with the removal of third molars or in patients who are congenitally missing third molars [6]. Other theories in this category attribute late mandibular anterior crowding to occlusal forces, eruption patterns or muscle function.…”
Section: Discussionmentioning
confidence: 99%